PENGARUH MUTASI, KOMPENSASI DAN MOTIVASI TERHADAP KEPUASAN KERJA KARYAWAN DI PT. PLN (PERSERO) WILAYAH SUMATERA BARAT AREA SOLOK - Hendri Dodi; Susi Evanita (Jurnal Riset Manajemen Bisnis dan Publik, 2014)
This study aimed to analyze the effect of mutation, compensation and motivation on employee job satisfaction in PT. PLN (Persero) West Sumatra   Solok Area. Type of research is causative. The population in this study were all employees at PT. PLN (Persero) West Sumatra Solok Area. Sampling based on Proportional Stratisfied Random Sampling. Analysis of data used path analysis and hypothesis testing using the F and  t test. Results of this study indicate that (1) mutation have a significant influence on employee job satisfaction in PT. PLN (Persero) West Sumatra Solok Area. (2) compensation had a significant influence on job satisfaction of employees at PT. PLN (Persero) West Sumatra Solok Area. (3) work motivation have a significant influence on job satisfaction of employees at PT. PLN (Persero) West Sumatra Solok Area. (4) mutation and compensation have a significant influence on employee job satisfaction in PT. PLN (Persero) West Sumatra Solok area indirectly through the variables of work motivation as an intervening variable, but the effect is smaller than the direct effect. From the research, it appears that the variable mutation have a greater influence than the variable compensation and work motivation. The next variable compensation have compared the effects of biggest than variable work motivation, and the variable that has the smallest effect in this study is the work motivation variables. So it can be interpreted variable mutation has a very important influence in improving employee job satisfaction in PT. PLN (Persero) West Sumatra Solok Area. Keywords: transfer, compensation, work motivation, job satisfaction.